Congenital sucrase-isomaltase deficiency: A case report - Santos-Silva,Rita (2014)
Background: Congenital sucrase-isomaltase deficiency (CSID) is an autosomal recessive disease characterized by absent sucrase activity with variable decrease in isomaltase activity. The prevalence of CSID in Portuguese population is unknown and there are few reported cases. Case report: We report the case of a six-month-old male infant admitted for chronic profuse diarrhea and failure to thrive that began after food diversification. The investigation showed that he had CSID. The therapeutic option was the addition of bakers yeast to the diet which was followed by complete resolution of symptoms and excellent weight recovery. Discussion: This case highlights the relevance of clinical observation and awareness in a condition where diagnosis is essentially clinical. The available therapeutic options are addressed with pragmatic use of bakers yeast.